Representasi Pelecehan Seksual Dalam Konsep Film Horor Religi Pada Film Qorin (2022) - Rivanda Daffauzan Thaufani; Sa'idah, Zahrotus (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The development of horror films in Indonesia continues to demonstrate innovation over time. One significant example is the film "Qorin" (2022), which introduces Islamic nuances with its storyline about mischievous jinn resembling humans. This research employs a qualitative approach to depict the social phenomena presented in the film, focusing on the levels of reality, representation, and ideology within scenes of harassment. Data collection methods involve observation, literature review, and documentation. The analysis, using John Fiske's semiotics, reveals reflective representations in the depiction of symbols conveying meaning. Horror films, including "Qorin," often depict supernatural elements, death, or mental illness, with antagonistic characters representing evil. With a duration of 109 minutes, "Qorin" provides audiences with an opportunity to comprehend that sexual harassment can occur in various situations and to anyone. Through this film, society is made aware of the diverse forms of sexual harassment, which may not have been recognized previously. Thus, horror films like "Qorin" serve not only as entertainment but also as a means to convey important social messages.